Penegakan Hukum Pelanggaran Kesehatan di Tengah Pandemi Covid-19 (Komparasi dengan Berbagai Negara) - Muhammad Arafah Sinjar (CV Rewang Rencang, 2022)
Mass mobilization is a problem that must be the main sizing that is considered during the Covid-19 Pandemic. This is because if not controlled properly, free mobilization actually becomes a medium of the spread of coronavirus that threatens public health in general. So ideally, the legal provisions become the vanguard in minimizing any potential transmission of Covid-19. However, this must also be accompanied by public awareness of health provisions. This study seeks to map the legality, problems to cases of health violations that occurred in the Indonesian community at the time of the momentum of the Covid-19 Pandemic. The authors will also compare the situation of law enforcement in other countries in particular Australia and the UK.